Formation of MgO during Chemical Magnesiation of Mg-Ion Battery Materials. (2nd June 2015) - Wang, Hao; Senguttuvan, Premkumar; Proffit, Danielle L.; Pan, Baofei; Liao, Chen; Burrell, Anthony K.; Vaughey, John T.; Key, Baris
Abstract : Chemical magnesiation of α-MnO2, V2 O5, Mo6 S8 and h-TiO2 using di-n-butylmagnesium/heptane and diphenylmagnesium/THF has been studied using a combination of long range (XRD) and short range (NMR) structural probes. XRD data shows no significant phase transformations in the bulk even though a color change has been observed for h-TiO2 and V2 O5 after treatment. 25 Mg MAS NMR shows significant amorphous MgO formation for samples with color change suggestive of concomitant transition metal reduction on the surface. No significant bulk magnesiation due to intercalation has been observed for any of the oxides treated with di-n-butylmagnesium/heptane or diphenylmagnesium/THF solution.